2000
DOI: 10.1016/s1350-6307(99)00005-9
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary analysis of failures in grey cast iron water pipes

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(32 citation statements)
references
References 8 publications
2
27
0
3
Order By: Relevance
“…Each pipe material undergoes failure in a different way. Studies have shown that the structural performance and behavior of the buried pipe depend on the type of backfill placed around the pipe, construction sequence, compaction control, surface loads, and the type of pipe material (flexible or rigid) (Makar, 2000;Rajani, 1996;Boot, 1998;Heger, 1985;Davies, 1999;Serpente, 1993).…”
Section: Objective 1 Data Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Each pipe material undergoes failure in a different way. Studies have shown that the structural performance and behavior of the buried pipe depend on the type of backfill placed around the pipe, construction sequence, compaction control, surface loads, and the type of pipe material (flexible or rigid) (Makar, 2000;Rajani, 1996;Boot, 1998;Heger, 1985;Davies, 1999;Serpente, 1993).…”
Section: Objective 1 Data Structurementioning
confidence: 99%
“…This construction method typically consists of placing pipes on bedding material and backfilling the trench. Studies have shown that the structural performance and behavior of the buried pipe is dependent on the type of backfill placed around the pipe, construction sequence, compaction control, surface loads, and the type of pipe material (Makar, 2000;Rajani, 1996;Boot, 1998;Heger, 1985;Davies, 1999;Serpente, 1993). The pipelines used in municipal wastewater systems are made of different types of material depending on suitability of the pipe location and design purposes.…”
Section: Wastewater Pipe Infrastructure Systemmentioning
confidence: 99%
“…The extensive use of metallic pipes in the industries such as oil, chemical, sugar, automotive, structural industries, paper and process is to transport high pressure liquids and gases [1][2][3][4][5][6][7][8][9][10][11][12][13]. It transmission of liquid is solely depends on the metallic pipes due to its higher strength and durability.…”
Section: Introductionmentioning
confidence: 99%
“…Algunas tuberías que en la actualidad formaban parte de las redes de distribución de agua han sido colocadas desde finales del siglo XIX (Makar, 2000), en la Figura 2.8 se muestra un esquema de la evolución de los materiales utilizados para la conducciones de las redes de distribución.…”
Section: El Deterioro De Las Conduccionesunclassified
“…Las tuberías de hierro fundido tienen el mayor número de fallos por kilómetro por año en Canadá, con rangos típicos de 0,39roturas/km/año (Makar, 2000). Como se ha mencionado, un factor importante es la edad de las tuberías.…”
Section: Figura 212 Fallos En Tubería De Hierrounclassified